(untitled) (Research, Society and Development, 2020)
UHT dairy beverages like the one in this study can have the technological application of soft serve ice cream or express as it is also known. In this study, the physical-chemical and microbiological characterization of the UHT dairy drink used as a liquid mixture for ice cream along the shelf- life, at three storage temperatures (21, 28 and 35 ° C), in addition, three batches of the same product were evaluated, with the same formulation, produced in sequence to verify the repeatability of the production process, product stability was perceived, despite a slight drop in pH, an increase in acidity and browning by a Maillard reaction occurred in products stored at a higher temperature. A rheological study was carried out and a pseudoplastic behavior was verified for the dairy drinks used as an input for soft serve ice cream, after extrusion the stability of the same was measured through a sedimentation and melting index showing good consumption conditions for all analyzed samples.